2023
DOI: 10.3390/agronomy13010237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tillage and N Applications on the Cassava Rhizosphere Fungal Communities

Abstract: Cassava (Manihot esculenta Crantz) is mainly cultivated in marginal land in the south of China where seasonal drought stress occurs frequently and the soil becomes more compact year by year. The study aimed to explore the effect of Fenlong tillage (FLT) combined with nitrogen applications on cassava rhizosphere soil particle composition and fungal community diversity. Conventional tillage (CT) was set as the control. The results indicated that the contents of clay and silt of the cassava rhizosphere soil were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…FT breaks the hardpan under the plow layer and creates a soil layer that is suspended and loosened, which leads to more favorable hydrothermal conditions, increases the availability of nutrients, water, and oxygen, and thus enhances microbial activities, thereby improving plant photosynthetic efficiency and crop yield [43][44][45][46]. FT has the characteristics of deep tillage and rotary grinding, which increase soil porosity and decrease soil bulk density [20,41,47].…”
Section: Ft Improve Sugarcane Growth and Yieldmentioning
confidence: 99%
See 3 more Smart Citations
“…FT breaks the hardpan under the plow layer and creates a soil layer that is suspended and loosened, which leads to more favorable hydrothermal conditions, increases the availability of nutrients, water, and oxygen, and thus enhances microbial activities, thereby improving plant photosynthetic efficiency and crop yield [43][44][45][46]. FT has the characteristics of deep tillage and rotary grinding, which increase soil porosity and decrease soil bulk density [20,41,47].…”
Section: Ft Improve Sugarcane Growth and Yieldmentioning
confidence: 99%
“…In this study, soil physical qualities, such as soil bulk density and porosity, were improved by FT. There were significant differences in the soil bulk density and porosity between the conventional and FT. A reduction in soil bulk density, an increase in soil porosity and water storage, and an improvement in available N and P after FT treatment indicated that FT could play an active role in the storage of soil nutrients [20,[44][45][46]50].…”
Section: Ft Improve Sugarcane Growth and Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the accumulation of self-toxic substances, such as phenolic acids, in soils from continuous cropping inhibits the growth of crops such as cucumbers, strawberries, and tobacco [10][11][12]. Many studies have also shown that continuous cropping significantly increases the relative abundance of fungal pathogens, leading to severe diseases in corn, soybeans, and melons [13][14][15].…”
Section: Introductionmentioning
confidence: 99%